Bizarre & beautiful eyes - Santa Fe Writers Group (Santa Fe, N.M. : John Muir Publications ; New York, N.Y. : Distributed to the book trade by W.W. Norton & Co. ; Bothell, WA : Distributed to the education market by the Wright Group, 1993)
Describes unique features of the sense of sight in several animals, including the dragonfly, penguin, dog, crab, and four-eyed fish.
Includes index.
Keywords: Vision -- Juvenile literature; Physiology, Comparative -- Juvenile literature; Physiology -- Juvenile literature; Vision; Physiology; Senses and sensation